Performance of a reforestation with native tree species of the Tamaulipas thorn scrub in degraded areas: Desempeño de una reforestación - Patiño-Flores, Ana María; Alanís-Rodríguez, Eduardo; Molina-Guerra, Víctor Manuel; Sigala Rodríguez, José Ángel; Jurado, Enrique; González-Rodríguez, Humberto; Aguirre-Calderón, Oscar Alberto (Instituto de Ecología, A.C., 2022)
The irrational use of natural resources has led to degradation of ecosystems. In northeastern Mexico, Tamaulipas thorn scrub has been affected by the removal of the vegetation cover due to different economic activities. Faced with this problem, strategies have been sought to try to reverse the damage caused to this community, for this reason, groups of managers and academics have resorted to reforestation with native species to know the requirements of each species and to be able to determine which are best for them. In the present study, the performance of a reforestation practice with native species of the Tamaulipas thorn scrub (Cordia boisieri, Caesalpinia mexicana, Eysenhardtia texana and Leucophyllum frutenscens) was evaluated. Evaluations were carried out every six months; from the beginning of the plantation until 41 months later. Survival was determined by the Kaplan-Meier method in addition to calculating growth rates for diameter, height, and cover. Overall survival was 49.4%. C. boissieri had the lowest survival (37.7%). C. boissieri and C. mexicana registered higher growth in diameter, all species stopped growing in diameter after 30 months. of this variable. Early growth rates in height were minimal, after month 20, C. mexicana showed was significantly taller. C. mexicana registered just over 10% of coverage. C. boissieri was the species with the lowest survival, and together with C. mexicana showed greater growth with respect to the rest of the species.